THE EFFECT OF ALOIN ON BLOOD SUGAR LEVELS IN STREPTOZOTOCIN-INDUCED WHITE MALE MICE (MUS MUSCULUS) - Rendri Bayu Hansah; Abdullah, Dessy; Thira Adiahni (Nusantara Hasana Journal, 2023)
Blood, a lack of insulin secretion, insulin metabolism and both. One herb that works as well as drop in blood glucose levels and repair the metabolism of insulin is an aloin founded in aloe vera. Aims. Knowing the effect of aloin on white male mice (Mus musculus) induced by STZ. Methode. The type of research is experimental with the approach "pre-post test control group design". The population in the study is the white male (Mus musculus) 2-3 months, weighing 20-40 grams by 24 mice obtained from the university's pharmacological laboratory of Andalas. This sample was random with 24 mice. Data analysis shows the results of distribution are abnormal so the analysis tests used to friedman and the hoc wilcoxon post test. Results. The highest levels of blood glucose include K (+) 1, which is 273.5 mg/dL are affected by aloin for a drop in blood glucose in STZ (mus musculus), based on wilcoxon's test on K (+) 2 on metformin, P1 aloin dose 0.5 mg/kg, P2 dose 1 mg/kg has the same strength in drop in blood glucose level 0.028 and the most decline in pre-post value in P2 aloin group 1 mg/dL. Conclusion. There are effects of metformin administration, aloin dose 0.5 mg/kg and 1 mg/kg on lower blood glucose, aloin dose 0.5 mg/kg and aloin 1 mg/kg could be used as replacement therapy.